Exploring the overlap between alopecia areata and major depressive disorder: epidemiological and genetic perspectives - Foo, Jerome Clifford; Redler, S.; Forstner, A. J.; Basmanav, F. B.; Pethukova, L.; Guo, J.; Streit, Fabian; Witt, Stephanie; Sirignano, Lea; Zillich, Lea; Awasthi, S.; Ripke, S.; et al. (Journal of the European Academy of Dermatology and Venereology, 2023)
Background Research suggests that Alopecia areata (AA) and Major Depressive Disorder (MDD) show substantial comorbidity. To date, no study has investigated the hypothesis that this is attributable to shared genetic aetiology. Objectives To investigate AA-MDD comorbidity on the epidemiological and molecular genetic levels. Methods First, epidemiological analyses were performed using data from a cohort of adult German health insurance beneficiaries (n = 1.855 million) to determine the population-based prevalence of AA-MDD comorbidity. Second, analyses were performed to determine the prevalence of MDD in a clinical AA case-control sample with data on psychiatric phenotypes, stratifying for demographic factors to identify possible contributing factors to AA-MDD comorbidity. Third, the genetic overlap between AA and MDD was investigated using a polygenic risk score (PRS) approach and linkage disequilibrium score (LDSC) regression. For PRS, summary statistics from a large MDD GWAS meta-analysis (PGC-MD2) were used as the training sample, while a Central European AA cohort, including the above-mentioned AA patients, and an independent replication US-AA cohort were used as target samples. LDSC was performed using summary statistics of PGC-MD2 and the largest AA meta-analysis to date. Results High levels of AA-MDD comorbidity were reported in the population-based (MDD in 24% of AA patients), and clinical samples (MDD in 44% of AA patients). MDD-PRS explained a modest proportion of variance in AA case-control status (R2 = 1%). This signal was limited to the major histocompatibility complex (MHC) region on chromosome 6. LDSC regression (excluding MHC) revealed no significant genetic correlation between AA and MDD. Conclusions As in previous research, AA patients showed an increased prevalence of MDD. The present analyses suggest that genetic overlap may be confined to the MHC region, which is implicated in immune function. More detailed investigation is required to refine understanding of how the MHC is involved in the development of AA and MDD comorbidity.